Berguru Islam ke Barat dan Pengembangan Perguruan Tinggi Keagamaan Islam di Indonesia - Abdul Zebar; Muhammad Irsan Barus; Candra Wijaya (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This paper describes the background of sending lecturers of Islamic Religious Education Perguruan Tinggi Keagamaan Islam (PTKI) to the Islamic West and their contribution to the development of ICM in Indonesia. Historically the background of sending Perguruan Tinggi Keagamaan Islam (PTKI) lecturers to the West was to change Islamic studies in Indonesia to become more comprehensive with more universal scientific methodologies and traditions. The shipping project was opposed by some Islamic leaders because it was considered to give birth to religious liberalism. On the other hand, the sending of lecturers was supported by a number of Islamic leaders to eliminate the tendency of sect sect of schools in Indonesia and efforts to integrate science in Islam. The contributions of alumni of Western Perguruan Tinggi Keagamaan Islam (PTKI) lecturers include (1) encouraging the entry of science courses in Perguruan Tinggi Keagamaan Islam (PTKI); (2) rationalizing the organizational structure of the campus, (3) updating the curriculum with more intensive Islamic studies with a variety of rich methodologies Renewing the curriculum; (4) publishing scientific journals; (5) open post graduate programs; and (6) changing studies at Islamic Higher Education from the pattern of schools to the non-Mazhabi approach.